Analisis Preferensi Konsumen Terhadap Keputusan Pembelian Fried Chicken Di Convenience Store (Studi Kasus : Circle K Kumbang, Kota Bogor) - Berutu, Febri; Fayza Andani; Rheisya Silvanny; Merin Ananda Permana Fitroh; Husnul Arrafi; Aliyah Rahma; Rasidin Karo Karo Sitepu; Tasya Angelita (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2024)
Modernization causes changes in food consumption, one of which is fast food, Fried chicken is a fast food menu that we often consume, this type of food is not only found in restaurants but also in convenience stores or convenience stores, one of which is Circle K. Problems at Circle K branches The Bogor City Kumbang is the lack of consumer buying interest in the fried chicken menu, not to mention its position close to competitors who sell similar products, namely Lawson, Mcdonald's and Burger King. This research aims to determine consumers' main attributes when buying fried chicken. The research location is Circle K Kumbang branch, Bogor City. This research uses a questionnaire in the form of a Google form as qualitative data. The sampling technique uses accidental sampling with a total of 60 respondents. The method used to answer this research is conjoint analysis. Conjoint analysis is a multivariate method used to study respondents' preferences for various types of goods (products, services and ideas). Data was processed with SPSS software. The results of the analysis show that the main attributes in the decision to purchase fried chicken include 1) consumers prefer the attribute of large pieces of chicken meat; 2) the texture attribute of thick, crispy chicken skin; 3) the appearance attribute of yellow skin; 4) packaging attributes using food boxes; and 5) selling price attribute > IDR 20,000.